HTRA1/lncRNA HTRA1-AS1 dominates in age-related macular degeneration reticular pseudodrusen genetic risk with no complement involvement - Farashi, Samaneh; Abbott, Carla J.; Ansell, Brendan R. E.; Wu, Zhichao; Altay, Lebriz; Arnon, Ella; Arnould, Louis; Bagdasarova, Yelena; Balaskas, Konstantinos; Chen, Fred K.; Chew, Emily; Chowers, Itay; et al. (Nature Communications, 2025)
Age-related macular degeneration (AMD) is a multifactorial retinal disease with a large genetic risk contribution. Reticular pseudodrusen (RPD) is a sub-phenotype of AMD with a high risk of progression to late vision threatening AMD. In a genome-wide association study of 2165 AMD+/RPD+ and 4181 AMD+/RPD- compared to 7639 control participants, both chromosomes 1 (CFH) and 10 (ARMS2/HTRA1) major AMD risk loci are reidentified. However association is only detected for the chromosome 10 locus when comparing AMD+/RPD+ to AMD+/RPD- cases. The chromosome 1 locus is notably absent. The chromosome 10 RPD risk region contains a long non-coding RNA HTRA1-AS1 (ENSG00000285955/BX842242.1) which colocalizes with genetic markers of retinal thickness. HTRA1-AS1 has a strong retinal eQTL signal, pinpointing the parafoveal photoreceptor outer segment layer. Whole genome sequencing of phenotypically extreme RPD cases identifies even stronger enrichment for the chromosome 10 risk genotype.